Handbook of ecological indicators for assessment of ecosystem health - Jorgensen, S. E. 1934-; Costanza, Robert; Xu, Fu-Liu (Boca Raton : CRC Press LLC Florence : Taylor & Francis Group [Distributor], 2005)
Annotation The field of ecosystem health explores the interactions between natural systems, human health, and social organization. As decision makers require a sound, modular approach to environmental management and sustainable development, ecosystem health assessment indicators are increasingly used across any number of applications. The Handbook of Ecological Indicators for Assessment of Ecosystem Health provides a comprehensive account and guidebook to ecological indicators for evaluating the health of a wide variety of ecosystems. The book presents a conceptual framework for selecting, evaluating, and validating ecological indicators of ecosystem health, such as thermodynamics, resilience estimates, exergy, and emergy indicators. This framework is applied in a series of chapters on major ecosystem types, including coastal areas, forests, wetlands, fisheries, and agricultural land. The authors take into account biodiversity, energy needs, ecological economics, and natural capital in their measurement of ecological health. Using material synthesized from a variety of books, journals, and private research, the book presents first-hand accounts of the indicators, used in several different types of ecosystems. Case studies highlight the advantages and disadvantages of each method as well.The Handbook of Ecological Indicators for Assessment of Ecosystem Health explains what is needed to apply the methods and indicators, including theoretical background and modeling techniques, to evaluate the state of a given ecosystem. It will be useful for a wide range of environmental managers, natural resource managers, land use planners, and policy makers in government and non-governmental organizations worldwide.
Keywords: Salud del ecosistema; Indicadores medioambientales